Acute and long-term immune responses to SARS-CoV-2 infection in unvaccinated children and young adults with inborn errors of immunity - García-García, Ana; Fortuny, Claudia; Fumadó, Victoria; Jordan, Iolanda; Ruiz-López, Laura; González-Navarro, Europa Azucena; Egri, Natalia; Esteve-Solé, Ana; Luo, Yiyi; Vlagea, Alexandru; Cabedo, Manel Monsonís; Launes, Cristian; et al. (Frontiers in Immunology, 2023)
Purpose: To describe SARS-CoV-2 infection outcome in unvaccinated children and young adults with inborn errors of immunity (IEI) and to compare their specific acute and long-term immune responses with a sex, age and severity-matched healthy population (HC). Methods: Unvaccinated IEI patients up to 22 years old infected with SARS-CoV-2 were recruited along with a cohort of HC. SARS-CoV-2 serologies and ELISpot were performed in the acute phase of the infection (up to 6 weeks) and at 3, 6, 9, 12 months. Results: Twenty-five IEI patients (median age 14.3years, min.-max. range 4.5-22.8; 15/25 males, 60.0%) and 17 HC (median age 15.3 years, min.-max. range 5.4-20.0; 6/17 males, 35.3%) were included. Pneumonia occurred in 4/25 IEI patients. In the acute phase, IgG, IgM and IgA were positive in all HC whereas only in half of IEI in whom it could be measured (n=17/25): IgG+ 58.8% (10/17) (p=0.009); IgM+ 41.2% (7/17)(p<0.001); IgA+ 52.9% (9/17)(p=0.003). Quantitative response (index) was also lower compared with HC: IgG IEI (3.1±4.4) vs. HC (3.5±1.5)(p=0.06); IgM IEI (1.9±2.4) vs. HC (3.9±2.4)(p=0.007); IgA IEI (3.3±4.7) vs. HC (4.6±2.5)(p=0.04). ELISpots positivity was qualitatively lower in IEI vs. HC (S-ELISpot IEI: 3/11, 27.3% vs. HC: 10/11, 90.9%; p=0.008; N-ELISpot IEI: 3/9, 33.3% vs. HC: 11/11, 100%; p=0.002) and also quantitatively lower (S-ELISpot IEI: mean index 3.2±5.0 vs. HC 21.2±17.0; p=0.001; N-ELISpot IEI: mean index 9.3±16.6 vs. HC: 39.1±23.7; p=0.004). As for long term response, SARS-CoV-2-IgM+ at 6 months was lower in IEI, qualitatively (3/8, 37.5% vs. 9/10 HC: 90.0%; p=0.043) and quantitatively in all serologies IgG, M and A (IEI n=9, 1.1±0.9 vs. HC n=10, 2.1±0.9, p=0.03; IEI n=9, 1.3±1.5 vs. HC n=10, 2.9±2.8, p=0.02; and IEI n=9, 0.6±0.5 vs. HC n=10, 1.7±0.8, p=0.002 –respectively-) but there were no differences in remaining time points. Conclusions: Our IEI pediatric cohort had a higher COVID-19 pneumonia rate than general population, with lower humoral and cellular responses in the acute phase, and weaker humoral responses at 6 months after infection compared with HC.